2006
DOI: 10.1007/s00125-006-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of Down’s syndrome in individuals with type 1 diabetes in Denmark: a nationwide population-based study

Abstract: Aims/hypothesis: In patients with Down's syndrome, dogma has long held that the prevalence of diabetes is increased. The aim of the present study was to determine the actual prevalence of Down's syndrome among type 1 diabetic patients. Subjects, materials and methods: The background population included all children born in Denmark between 1981 and 2000. Registryvalidated and clinical data on type 1 diabetes and Down's syndrome diagnoses were obtained from the National Disease Register and Danish Cytogenetic Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 11 publications
5
83
0
2
Order By: Relevance
“…This is very close to the prevalence of 0.38% reported in a study of the Danish population [2] that suggested an association with HLA genotypes and the possibility of genetic risk loci on chromosome 21. The 0.38% prevalence of Down's syndrome in our population of diabetic patients was much higher than the Down's syndrome prevalence in other general populations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is very close to the prevalence of 0.38% reported in a study of the Danish population [2] that suggested an association with HLA genotypes and the possibility of genetic risk loci on chromosome 21. The 0.38% prevalence of Down's syndrome in our population of diabetic patients was much higher than the Down's syndrome prevalence in other general populations.…”
Section: Discussionsupporting
confidence: 88%
“…The Danish study [2] found that the onset of type 1 diabetes occurred at an earlier age of 6 years in Down's syndrome patients compared with 8.2 years in the background population. In our study, we found a smaller difference of 8.2 vs 8.4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a questionnaire-based study of 20,362 patients with Down's syndrome in the U.K. and U.S., the prevalence of diabetes diagnosed before age 20 years in the Down's syndrome population was some six times higher than expected (5), and other studies suggest an approximate fourfold increase in childhood diabetes (3,6). A more recent population-based study of the prevalence of type 1 diabetes in Down's syndrome in Denmark demonstrated a fourfold increased risk of type 1 diabetes in children with Down's syndrome (7). Although classification was generally made on clinical grounds alone, most appear to have type 1 diabetes.…”
mentioning
confidence: 90%
“…We have recently demonstrated the prevalence of Down's syndrome in T1D to be four times increased, supporting genes on chromosome 21 to be responsible for this higher prevalence. 20 Such genes might also be important in T1D in general.…”
Section: Discussionmentioning
confidence: 99%